Faktor Determinan Independensi Komisaris, Komite Audit, Struktur Kepemilikan, dan Islamic Social Reporting pada Nilai Perusahaan Jakarta Islamic Index (JII) - Yunistiawati, Friska; Badina, Tenny; Rosiana, Rita (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
This study aims to analyze the effect of the variables of the audit committee, independent board of commissioners, institutional ownership, managerial ownership, Islamic Social Reporting, and company financial performance in influencing firm value. The sample of this study is a company listed on the Jakarta Islamic Index (JII) for the period 2016 to 2020 using the multiple analysis method. This study provides results that independent commissioners, managerial ownership, and Islamic social reporting have a positive effect on firm value. Meanwhile, the audit committee, institutional ownership, and the company's financial performance as proxied by ROA do not have a significant effect on firm value. This study has the implication that firms listed in the Jakarta Islamic Index (JII) are obliged to disclose sharia social responsibility towards the environment and society.